Recurrent 8-Year Ongoing Unilateral Breast Seroma Formation after PIP Implant Removal—A Case Report and Review of the Literature - Kästner, Sonja; Paprottka, Felix Julian; Gonser, Phillipp; López, Manuel De Villegas; Kaye, Kai Oliver (The Surgery Journal, 2018)
Late seroma formation is a rare complication after implant-based breast enlargement surgery and even less frequent after implant removal. This case report presents a case of painful recurrent seroma formation after the removal of a ruptured Poly Implants Prothèse implant.A 52-year-old patient presented herself in our clinic with a clinical history of recurrent unilateral seroma of the right breast over a period of 8 years after the initial unilateral implant removal. Removal of the remaining implant and complete bilateral capsulectomy was performed. Intraoperative findings revealed a macroscopically thickened capsule with signs of chronic inflammation on the affected side. The clinical history and the macroscopic appearance of the capsule demanded histopathological exclusion of a possible anaplastic large cell lymphoma.Histopathological and microbiological analysis of the capsule and encapsulated material revealed no signs of malignancy or infection. Immediate soft tissue reconstruction of the breast was successfully performed using autologous fat transfer. An aesthetically satisfying result regarding symmetry and volume was achieved, and no further seroma formation was observed within a 6-month follow-up period.Level of evidence: V, Case Report.
Keywords: ALCL; late seroma; breast augmentation; PIP; implants; capsular contracture; autologous fat transfer; breast reconstruction; implant rupture